Melchior Wankowicz : Poland's master of the written word - Ziolkowska-Boehm, Aleksandra, 1949- (Lexington Books, 2013)
In Melchior Wankowicz: Poland's Master of the Written Word, Aleksandra Ziolkowska-Boehm examines the life and writing of famous Polish writer Melchior Wankowicz, author of legendary work "The Battle of Monte Cassino". Melchior Wankowicz was famous for creating his theory of reportage, i.e. the "mosaic method" where the events of many people were implanted into the life of one person. In this book, Ziolkowska-Boehm offers a critical examination of Wan>